A metal sulfide photocatalyst composed of ubiquitous elements for solar hydrogen production. Issue 47 (20th May 2016) - Shiga, Y.; Umezawa, N.; Srinivasan, N.; Koyasu, S.; Sakai, E.; Miyauchi, M.
Abstract : A visible-light-sensitive tin sulfide photocatalyst was designed based on a ubiquitous element strategy and density functional theory (DFT) calculations. Abstract : A visible-light-sensitive tin sulfide photocatalyst was designed based on a ubiquitous element strategy and density functional theory (DFT) calculations. Computational analysis suggested that tin monosulfide (SnS) would be more efficient than SnS2 as a photocathode for hydrogen production because of the low ionization potential and weak ionic character of SnS. To test this experimentally, nanoparticles of SnS were loaded onto a mesoporous electrode using a wet chemical method, and the bandgap of the synthesized SnS quantum dots was found to be tunable by adjusting the number of successive ionic layer adsorption and reaction (SILAR) cycles, which controls the magnitude of the quantum confinement effect. Efficient hydrogen production was achieved when the bandgap of SnS was wider than that of the bulk form.